IN VITRO EVALUATION OF DENTINE ADHESIVE RESISTANCE AFTER APPLYING TWO IRRIGATION SEQUENCES - Marchant, Carlos; Brito, Daniela; Durán, Bruno; Vidal, Juan Carlos; Navarrete, Ángel (Applied Sciences in Dentistry, 2020)
Objective: To evaluate the bond-strength (MPa) of an adhesive system to intracameral dentin after 2 different endodontic irrigation sequences. Material and Methods: An in vitro double-blinded experimental cross-over study was conducted. 23 teeth were extracted, and sectioned, exposing the pulp chamber. Samples were separated into three groups: the first group (control) used a 0.9% saline solution; in the second group, the conventional sequence of irrigation of the University of Valparaíso was employed (5% NaOCl -18% EDTA-0.9% saline solution); and finally the third group, the experimental sequence was employed (5% NaOCl, 18% EDTA and 15% saline solution). The sealing technique was then conducted using universal 3M ESPE Single Bond adhesive and Filtek Z350 resin. Subsequently, the bond-strength test was performed in a microtensile, until fracture. Results: The control group had the highest values of frequency of adhesive and cohesive failure compared to the conventional and experimental group but presented a statistically non-significant association. As for the irrigation protocols, they did not show a major difference in their adhesive bond-strength when compared. Conclusion: The results of this study conclude that the adhesive resistance is not significantly modified by different irrigation protocols.